Tetanus. A review of 54 cases. - Narciso, J; Abecasis, P; Ribeiro, J; Mota, J C (Acta Médica Portuguesa, 1992)
Tetanus continues to be a frequent illness with a high rate of mortality which mainly affects the elderly. In view of this, 54 cases treated in the ICU between 1983 and 1991 were studied. The clinical support with mechanical ventilation and the use of new drugs, which allowed for a more satisfactory sedation and muscular relaxation, and which permitted the control of the autonomic overactivity, were the most determinant factors in the reduction of mortality verified in the late years of our practice.